Implementation of Smart Grid Technology to Increase The Efficiency of Electrical Energy Distribution In Urban Areas - Nainggolan, Jekly Boy (Journal of Electrical Engineering, 2025)
The rapid growth of urban populations and economic activities has significantly increased electricity demand, placing heavy pressure on conventional distribution systems that are prone to high power losses, voltage instability, and limited fault detection capabilities. This research investigates the application of smart grid technology as a solution to enhance the efficiency, reliability, and sustainability of electricity distribution in urban areas. A comparative simulation was conducted using MATLAB/Simulink and ETAP to evaluate two distribution models: a conventional system and a smart grid-enabled system incorporating advanced metering infrastructure (AMI), real-time monitoring sensors, adaptive load management, and renewable energy integration. The results indicate that smart grid implementation reduces average power losses by nearly 40%, improves voltage stability with deviations reduced from ±7% to ±3%, and enhances system reliability as reflected in reduced SAIDI and SAIFI indices. Furthermore, the integration of rooftop photovoltaic (PV) generation contributes to peak load reduction while supporting the transition towards sustainable energy systems. These findings highlight the contextual relevance of smart grid adoption in Indonesia, where infrastructure and regulatory challenges remain, and provide practical recommendations for utilities and policymakers. The novelty of this study lies in its focus on urban distribution networks in developing countries, offering a localized model that integrates efficiency improvements, renewable energy penetration, and adaptive control strategies to support sustainable urban energy development.